Poisson-model Analysis of Power Alternation in Africa - Kpegli, Yao Thibaut; Anne, Bator (International Journal of Economics and Financial Issues, 2019)
In Africa, there are many countries that rarely know the change of their president. The aim of this paper is to study the economic and non-economic determinants of number of power alternation in Africa over the period 1990-2015. The poisson regression is used. The results indicate that the growth of the gross domestic product per capita has a negative impact on the number of political change while the democracy index and the coup have a positive influence. Keyswords: poisson model, power alternation, Africa JEL Classifications: D72, C53 DOI: https://doi.org/10.32479/ijefi.6335